2019
DOI: 10.3847/1538-4357/ab0417
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Transition Region Explosive Events and Their Relationship to Network Jets

Abstract: Recent imaging observations with the Interface Region Imaging Spectrograp (IRIS) have revealed prevalent intermittent jets with apparent speeds of 80-250 km s −1 from the network lanes in the solar transition region (TR). On the other hand, spectroscopic observations of the TR lines have revealed the frequent presence of highly non-Gaussian line profiles with enhanced emission at the line wings, often referred as explosive events (EEs). Using simultaneous imaging and spectroscopic observations from IRIS, we in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
(58 reference statements)
7
27
0
Order By: Relevance
“…Such profiles can be produced in magnetic reconnection that proceeds via plasmoid instability characterized by multiple magnetic islands and acceleration sites (Innes et al 2015). Our results could be understood in the similar way of a recent work by Chen et al (2019a), who found that non-Gaussian Si iv spectra with enhancement at the blue wing are found in locations on network jets away from the footpoints and those showing enhancement only at the red wing of the line are often located around the jet footpoints. Here, the spectral slit might not capture equally magnetic islands moving at both directions and thus the enhance-ment at two wings are not balance.…”
Section: Heating Eventssupporting
confidence: 86%
“…Such profiles can be produced in magnetic reconnection that proceeds via plasmoid instability characterized by multiple magnetic islands and acceleration sites (Innes et al 2015). Our results could be understood in the similar way of a recent work by Chen et al (2019a), who found that non-Gaussian Si iv spectra with enhancement at the blue wing are found in locations on network jets away from the footpoints and those showing enhancement only at the red wing of the line are often located around the jet footpoints. Here, the spectral slit might not capture equally magnetic islands moving at both directions and thus the enhance-ment at two wings are not balance.…”
Section: Heating Eventssupporting
confidence: 86%
“…Although causes of line asymmetry and line wing broadening have been studied by many authors (Peter, 2010;Tian, McIntosh, & De Pontieu, 2012;Tian, McIntosh, Xia, et al, 2012;Leenaarts et al, 2013;Polito et al, 2015;Chen et al, 2019), there is no well unified explanation for the asymmetry of the line profile yet. In this work, the observed asymmetric and double-peak profiles of the Si IV spectral line should result from the magnetic reconnection process (Innes et al, 1997;Ning & Guo, 2014;Chen et al, 2019). According to 10.1029/2019JA027017…”
Section: Discussionmentioning
confidence: 99%
“…Although causes of line asymmetry and line wing broadening have been studied by many authors (Peter, 2010;Tian, McIntosh, & De Pontieu, 2012;Tian, McIntosh, Xia, et al, 2012;Leenaarts et al, 2013;Polito et al, 2015;Chen et al, 2019), there is no well unified explanation for the asymmetry of the line profile yet. In this work, the observed asymmetric and double-peak profiles of the Si IV spectral line should result from the magnetic reconnection process (Innes et al, 1997;Ning & Guo, 2014;Chen et al, 2019). According to the numerical experiments of Ni et al (2016), we created the synthetic profile of the Si IV line that supposes to be observed in the jet and noticed that the reconnection outflows and the existence of the plasmoids could account for the asymmetry and multiple-peak feature of the spectral line profile.…”
Section: Discussionmentioning
confidence: 99%
“…For the former, IRIS and SDO/AIA observations indicate that spicules appear to be the root of some coronal propagating disturbances (Pant et al, 2015;Samanta, Pant, and Banerjee, 2015;Bryans et al, 2016); however, it remains unclear whether these propagating disturbances are caused only by waves or whether flows of heated material are also injected into the corona during such events. Concerning network jets, it has been argued that they are the TR counterpart of spicules (Tian et al, 2014d;Narang et al, 2016;Chen et al, 2019b;Qi et al, 2019) with fast apparent motions (> 100 km s −1 ); nonetheless the combination of models and observations (De Pontieu, Martínez-Sykora, and Chintzoglou, 2017;Chintzoglou et al, 2018) suggest that many of these jets may actually be rapidly propagating heating fronts along spicules, rather than caused by mass motions. Further modeling and observations are required to settle these issues, and thereby address the energy and mass flux associated with these events.…”
Section: Solar Jets and Surgesmentioning
confidence: 99%